2021
DOI: 10.3390/ani11082211
|View full text |Cite
|
Sign up to set email alerts
|

Discriminant Canonical Tool for Differential Biometric Characterization of Multivariety Endangered Hen Breeds

Abstract: This study aimed to develop a tool to perform the morphological characterization of Sureña and Utrerana breeds, two endangered autochthonous breeds ascribed to the Mediterranean trunk of Spanish autochthonous hens and their varieties (n = 608; 473 females and 135 males). Kruskal–Wallis H test reported sex dimorphism pieces of evidence (p < 0.05 at least). Multicollinearity analysis reported (variance inflation factor (VIF) >5 variables were discarded) white nails, ocular ratio, and back length (Wilks’ la… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 23 publications
(24 citation statements)
references
References 55 publications
0
24
0
Order By: Relevance
“…The logistic regression/COX model showed that FVTC, whether as a continuous or a categorical variable, was positively correlated with the occurrence of AKI, ICU mortality, and in-hospital mortality when unadjusted. The results of VIFs prior to multivariate analysis were listed in Supplementary Table S1 , with VIFs between 1 and 5 for each variable, illustrating the absence of multicollinearity problems ( 27 ). After adjusted by age, weight, gender, SOFA score, type of patient's first admission to ICU, ventilator use, vasopressor use, comorbidities, source of infection, infectious pathogen, co-infection with Gram-negative bacilli, duration of vancomycin use, vital signs, and the laboratory test result, FVTC was still a risk factor with the occurrence of AKI (OR: 1.02; 95% CI:1.01–1.04), ICU mortality (HR:1.02; 95% CI:1.01–1.03), and in-hospital mortality (HR:1.02; 95% CI:1.01–1.03), which means that for every unit increase in FVTC, the risk of AKI, ICU and in-hospital mortality increases by 1.02 times.…”
Section: Resultsmentioning
confidence: 99%
“…The logistic regression/COX model showed that FVTC, whether as a continuous or a categorical variable, was positively correlated with the occurrence of AKI, ICU mortality, and in-hospital mortality when unadjusted. The results of VIFs prior to multivariate analysis were listed in Supplementary Table S1 , with VIFs between 1 and 5 for each variable, illustrating the absence of multicollinearity problems ( 27 ). After adjusted by age, weight, gender, SOFA score, type of patient's first admission to ICU, ventilator use, vasopressor use, comorbidities, source of infection, infectious pathogen, co-infection with Gram-negative bacilli, duration of vancomycin use, vital signs, and the laboratory test result, FVTC was still a risk factor with the occurrence of AKI (OR: 1.02; 95% CI:1.01–1.04), ICU mortality (HR:1.02; 95% CI:1.01–1.03), and in-hospital mortality (HR:1.02; 95% CI:1.01–1.03), which means that for every unit increase in FVTC, the risk of AKI, ICU and in-hospital mortality increases by 1.02 times.…”
Section: Resultsmentioning
confidence: 99%
“…Phenotypic variation of local animal resources indicates a genetic diversity that may be worth conserving for future uses while better understanding of the external features helps to facilitate the implementation of conservation policies aimed to ensure local resources survival [18]. Morphometric and phaneroptic approaches may be fundamental in the management of poultry considering the fact that they are fast and economically profitable [44]. The preponderance of more female birds in the present study could be attributed to the fact that smallholder poultry farmers normally keep more hens for the purpose of procreation, whereas the cocks are mostly slaughtered for consumption or sold to generate family income.…”
Section: Discussionmentioning
confidence: 99%
“…It is congruous to the submission of Vignal et al [6] that the prevalence of a particular colour could be attached to social-cultural value without any proven relationship with a biological function. This was buttressed by the report of González Ariza et al [44] that certain phaneroptic variables may be associated with consumers' trends and their cultural preferences.…”
Section: Decision Trees Of the Data Miningmentioning
confidence: 99%
See 1 more Smart Citation
“…In this regard, the variance overinflation probably derived from the fact that highly sex imbalanced populations were being modelled comprising both sexes altogether. The literature has suggested that the aptitude to which specific poultry genotypes are destined may condition the use of a greater number of animals of one sex or another [ 56 ].…”
Section: Growth and Performance Modellingmentioning
confidence: 99%